Introduction: Communicating time and place on digital media—Multi-layered temporalities & (Re)localizations. (September 2015) - Georgakopoulou, Alexandra
Abstract: The Introduction to this Special Issue identifies a gap of empirical insights into how the digital media-enabled drastic redefinitions of time and space/place experience impact on communication choices. This is despite extensive theorizing of time and space/place in media & cultural studies on the one hand and, on the other hand, despite a thriving line of (socio)linguistic inquiry into how physical time and space/place are made socio-culturally meaningful in specific communication acts. In the light of this, I outline the main aims and motivations for bringing together emerging discourse and sociolinguistic perspectives on communicating time and space/place in digital media, with this collection of papers. In discussing the seven contributions and their methodological and analytical commonalities but also diversity, I show how they attend to the linguistic and multi-modal choices with which digital media users and producers orient to, negotiate, foreground or challenge aspects of the here & now as well as of any other places and times invoked in their communication. In addition to this, all contributions interrogate the ways in which semiotic choices related to time and place shape and are informed by individuals' identities, audience assumptions & the (re)formation of online communities. The main themes in this respect include: – Communicating time and place of private experiences in (semi)-public forums with a potential for unknown and multiple audiences to tune in and become part of the communication; – Creating co-presence and reaffirming relationships and communities through discourse activities of marking or evoking time and place; – The often competing inter-relations between online and offline time and place; – The interdependence between the spatial architecture of digital media environments and any communication acts in them, which often involves a process of turning online spaces into inhabited places . I claim that all contributions demonstrate the need for conceptual and analytical tools and methods that are well-suited to capturing multi-layered arrangements of communicating time and place in digital environments.